Influenza equina en Chile (1963- 1992) - Berríos E., Patricio; Celedón V., María O. (Avances en Ciencias Veterinarias, 1992)
In this general article is presented the situation of equine influenza in Chile from 1963, when the first outbreak of this disease was described. Equine influenza has been reported several times from then; main outbreaks have occurred in 1977, 1985 and recently on march of 1992. The presentation of equine influenza in our country is discussed en relation to continental epizootics. Equine influenza virus has been isolated only in three oportunities: in 1977 it was isolated the strain A/equi/1/Santiago, Chile/1977 (H7 N7); in 1985 the strain A/equi/2/Santiago, Chile/1985 (H3 N8), and in 1992 the strain A/equi/2/Quillota, Chile/1992 (H3 N8). Beside, it is discussed different studies about the use of hemoagglutination inhibition test, viral seroneutralization and single radial hemolisis test; preliminary characterization of chilean strains of equine influenza virus and post vaccinal response to national and international vaccines against equine influenza. Key words: Virus, influenza, horses. Palabras claves: Virus, influenza,equino.